The Double-Edged sword of being the ‘minority other’ applicant: - Heer, Simran (2022)
The purpose of this study is to underpin white normative standards that typically dominate recruitment processes for graduate schemes within the UK, and how they foster ‘othering’. It aims to do this via a unique angle of focus; through exploring complex biographies of different ethnic minorities. It takes their individual perceptions and experiences of recruitment processes into consideration. This study adopts qualitative methodology. This qualitative methodology is conducted to peruse the thoughts and feelings of the participants in this study. The abundance of organisational literature does not empirically address how whiteness can lead to a less inclusive workplace, and this illuminates existing gaps in literature. To help address this interviews were conducted via 1-1 face-to-face meetings and whereby, not possible these interviews were held via Microsoft Teams. Participants who identified as an ethnic minority and as a graduate were recruited. The study established that there are indeed instances whereby, ethnic minority individuals endure disadvantages during the recruitment process. This is due to a range of mitigating socioeconomic background features or intersectional boundaries. Additionally issues of discrimination during hiring processes, as well as career progression and homogenisation were also key variables that fostered occurrences of marginality. Equally, there are instances where marginality has not always occurred for the participants in this study, but marginalised instances seems to prevail for the majority. This dissertation puts forward suggestions for future research: my research could be further re-evaluated or expanded empirically for a more extensive insight into the topic raised.